Strategi Komunikasi Politik Legislator Lokal Dalam Mempertahankan Elektabilitas di Kota Semarang - Dimara, Damarjati; ., Mubarok; Kurdaningsih, Dian Marhaeni (Universitas Brawijaya, 2024)
This research is a case study of the success of the political communication strategy of a local legislator named Kadarlusman in the city of Semarang in maintaining his political electability. The paradigm used in this research is the constructivism paradigm. Data collection techniques in this research are interviews and observation to obtain primary data as well as documentation and literature study to obtain secondary data. The theory used in this research is the social exchange theory of John Thibaut and Harold Kelley which highlights the exchange of messages, responses and rewards between individuals and dyadic groups in social interactions. The results of this research show the success of a local legislator named Kadarlusman as Chair of the Semarang City DPRD in maintaining his political electability in the City of Semarang through a Political Communication Strategy, especially in the Electoral District 5 area. The series of Political Communication activities carried out was the City DPRD Chairperson Cup E-Sports Mobile Legends Tournament. Semarang, Kopimi Outlet UMKM Bazaar, Wonosari Village, Cultural Carnival in the framework of the KH Haul. Syafi'I Piyoronegoro, and Pak Pilus' interactions with residents of RW 10. The results of this research were analyzed to determine the social exchanges that occurred in the context of interpersonal communication and it can be concluded that his political communication strategy was successful. Kadarlusman has received the most votes in Semarang City in legislative elections since 2014, 2019 and 2024.